La gallina di Petronio e le altre - Schievenin, Romeo (Exemplaria Classica, 2010)
The episode of the chicken and peahen’s eggs presents some technical factors that on one hand allow to delete without hesitation a gloss of the Codex Traguriensis, on the other involve interesting implications on the literary level for the interpretation of the whole episode.